Plastic and aesthetic values advertising and its impact on the environment and society - riham Fahim (Journal of Architecture, Art & Humanistic Science, 2017)
The new technologies added new capabilities to people that were not available before, and increased their production of the art creation. The technology added the new arts like Cinema, which considered as a technology-product, and introduced new devices representing art works like TV and Computers. There new tools helped to discover ways and forms of beauties and developed new aesthetic values were not exist before in the old times and civilizations. This thesis represent the visual, aesthetic and plastic values for the 3d ads and its impacts on the environment and society through the ethic and behaviour values. It shows the marketing success of creative samples of products as results of the study and analysis of the site space and understanding of the changing environmental factors (Countryside, beaches, deserts) and develop ideas for environmental friendly samples, and local geographic materials, and develop idea and environmental friendly samples that best suit to each geographical area.